An atlas-guided automatic planning approach for rectal cancer intensity-modulated radiotherapy. (23rd July 2021) - Peng, Jiayuan; Chen, Yuanhua; Zhao, Jun; Wang, Jiazhou; Xia, Xiang; Cai, Bin; Mazur, Thomas R; Zhu, Ji; Zhang, Zhen; Hu, Weigang
Abstract: We try to develop an atlas-guided automatic planning (AGAP) approach and evaluate its feasibility and performance in rectal cancer intensity-modulated radiotherapy. The developed AGAP approach consisted of four independent modules: patient atlas, similar patient retrieval, beam morphing (BM), and plan fine-tuning (PFT) modules. The atlas was setup using anatomy and plan data from Pinnacle auto-planning (P-auto) plans. Given a new patient, the retrieval function searched the top similar patient by a generic Fourier descriptor algorithm and retrieved its plan information. The BM function generated an initial plan for the new patient by morphing the beam aperture from the top similar patient plan. The beam aperture and calculated dose of the initial plan were used to guide the new plan optimization in the PFT function. The AGAP approach was tested on 96 patients by the leave-one-out validation and plan quality was compared with the P-auto plans. The AGAP and P-auto plans had no statistical difference for target coverage and dose homogeneity in terms of V 100% ( p = 0.76) and homogeneity index ( p = 0.073), respectively. The CI index showed they had a statistically significant difference. But the ΔCI was both 0.02 compared to the perfect CI index of 1. The AGAP approach reduced the bladder mean dose by 152.1 cGy ( p < 0.05) and V 50 by 0.9% ( p < 0.05), and slightly increased the left and right femoral head mean dose by 70.1 cGy ( p < 0.05) and 69.7 cGy ( p < 0.05), respectively. This work developed an efficient and automatic approach that could fully automate the IMRT planning process in rectal cancer radiotherapy. It reduced the plan quality dependence on the planner experience and maintained the comparable plan quality with P-auto plans.